Selective intra-arterial brain cooling improves long-term outcomes in a non-human primate model of embolic stroke: Efficacy depending on reperfusion status. Issue 7 (July 2020) - Wu, Di; Chen, Jian; Hussain, Mohammed; Wu, Longfei; Shi, Jingfei; Wu, Chuanjie; Ma, Yanhui; Zhang, Mo; Yang, Qi; Fu, Yongjuan; Duan, Yunxia; Ma, Cui; et al.
Nearly all stroke neuroprotection modalities, including selective intra-arterial cooling (SI-AC), have failed to be translated from bench to bed side. Potentially overlooked reasons may be biological gaps, inadequate attention to reperfusion states and mismatched attention to neurological benefits. To advance stroke translation, we describe a novel thrombus-based stroke model in adult rhesus macaques. Intra-arterial thrombolysis with tissue plasminogen activator leads to three clinically relevant outcomes – complete, partial, and no recanalization based on digital subtraction angiography. We also find reperfusion as a prerequisite for SI-AC-induced benefits, in which models with complete or partial reperfusion exhibit significantly reduced infarct volumes, mitigated neurological deficits, improved upper limb motor dysfunction in both acute and chronic stages; however, no further neuroprotection is observed in those without reperfusion. In summary, we discover reperfusion as a crucial regulator of SI-AC-induced neuroprotection and provide insights of long-term functional benefits in behavior and imaging levels. Our findings could be important not only for the translational prerequisite and potential molecular targets, but also for this thrombus-thrombolysis model in monkeys as a powerful tool for further translational stroke studies.